Osteocutaneous Second-Toe Free Flap as Alternative Option for Repair of Anterior Oronasal Fistula: Long-Term Results in Selected Patients. Issue 6 (September 2016) - Pribaz, Julian J.; Singh, Mansher; Stephens, Willie; Caterson, E.J.
Abstract : Introduction: Palatal fistulas anterior to the incisive foramen, generally seen as a complication of cleft lip and cleft palate repair, can be extremely difficult to repair. The requirements of the defect necessitate nasal lining, oral lining, and bone for maxillary arch continuity. Local pedicled flap has limited use in such patients with extensive scarring from previous surgeries. The authors have recently described a technique involving osteocutaneous free-tissue transfer of second toe for anterior oronasal fistulas. Methods: The authors describe their experience of patients with anterior oronasal fistula who underwent osteocutaneous free-tissue transfer of second toe. Between 1991 and 2014, 3 patients with oronasal fistulas were operated utilizing bilaminar osteocutaneous free tissue transfer. Described are the surgical decision making, postoperative course, and surgical outcomes. Results: The mean age of the patients at the time of the procedure was 45.3 years with a mean follow-up of 12.6 years. All the patients had significant improvement of their regurgitation and speech difficulty. One of the patients with very large fistula had recurrence of the fistula which was repaired by local advancement of the original free flap. Conclusions: Use of osteocutanous second-toe free flap can provide complete coverage of the fistula with nasal and oral skin lining and provides an alternative option for complicated anterior oronasal fistula.